Reconversion de friches militaires : le refuge culturel comme dispositif unique en son genre - Fabien Jakob (Revue de Géographie Alpine)
Through different official communication channels (websites, brochures, reports, etc.), minutes of meetings, interviews, this research, conducted between May 2015 and October 2017, examines an operation to reassign a vast underground galleries and military fortifications network located in the Swiss Alps into a unique scheme dedicated to the cultural heritage preservation. Thanks to a pragmatic approach inspired by the sociology of emancipation (Boltanski & Thévenot, 1991) under which the commitment to action is coordinated around a shared conception of common good (civic, industrial, inspired, fame, domestic and market), it aims at analyzing the heterogeneous representations and actions registers which are mobilized during this reassignment attempting a compromise between technical, cultural dimensions, market concerns, political issues and diplomatic aspirations.